Utilization of the Byproduct from Phonolite Rock Exploitation in the Production of Ceramic Bodies - Abusriwil, Halima AlShaibani; Ftis, Numidia Fouad (Journal of natural sciences, life and applied sciences, 2025)
This study aims to evaluate the potential use of the byproduct generated from the exploitation of phonolite rocks in the Gharyan region of Libya as an alternative fluxing material in the production of ceramic bodies, with the goal of promoting sustainability and reducing reliance on imported materials. An experimental approach was adopted to prepare ceramic mixtures using local raw materials. Physical, chemical, and mineralogical analyses were conducted for both local feldspar and the phonolite byproduct. Chemical analysis results showed that the combined content of sodium, potassium, and calcium oxides in the phonolite reached approximately 16%, making it effective in enhancing ceramic properties. Six ceramic mixtures with varying proportions of feldspar and phonolite were prepared, and the physical and mechanical properties of the samples were studied before and after firing at 1200°C and 1250°C. The results indicated that the mixture containing 50% feldspar and 50% phonolite (of the fluxing materials) achieved the best performance, with a low water absorption rate (0.1%) and high modulus of rupture, without any deformation or warping. The study recommends expanding the use of phonolite byproducts in ceramic industries due to their positive impact on product quality and reduction of environmental and economic costs. Further research is also encouraged to explore the applications of phonolite in other industries such as glass and ceramic glazes.